\(rbc\)L DNA region revealed as the best DNA barcode for identification of \(Mahonia\) and \(Berberis\) species (Berberidaceae) - Trang, Nguyen Thi Phuong (Academia Journal of Biology, 2021)
Berberidaceae contains 17 genera and nearly 650 species, in which the genus Berberis and the genus Mahonia are sisters with a very close relationship and share many similar characteristics. In the past, the two genera were merged into the genus Berberis. At present, the Berberidaceae is at risk and is prioritized for conservation, especially the species of Mahonia and Berberis. In the fact, identification for the Berberidaceae species based on the morphology of parts for sale (such as roots, stems, leaves) without reproductive organs (flowers and fruits) is impossible.In recent years, molecular biology techniques are being applied widely and effectively in research on the evolution, classification and genetic diversity of populations. Study based on DNA has highly accurate and particularly useful for closely related species which morphological observations are not sufficient to distinguish. Results from DNA analysis allow authentic species, populations or individuals from un-intact specimens accurately and especially, it is not affected by objective factors such as the environment or human.In this study, we assessed the taxonomy ability of three commonly DNA barcoding regions used for classification including rbcL, trnH-psbA and ITS2 on 12 samples of the Berberidaceae family, in which 7 samples are genus Mahonia, 4 samples are genus Berberis and one sample of Epimedium was used as the control sample. The results of the study will contribute to the selection of suitable DNA barcode for the identification of Mahonia and Berberis samples.The results demonstrated that the rbcL region showed the most obvious ability to distinguish the 12 Berberidaceae species. The ITS2 sequences of Berberis julianeae and Mahonia bealei of Vietnam were submitted to GenBank with accession numbers MT073031 and MT008067, respectively. The sequence of rbcL of Mahonia bealei was also submitted to GenBank with accession number MT457415.1.